Kesantunan berbahasa para Kader Posyandu dalam pelaksanaan layanan informasi - Endang Wiyanti; Yulian Dinihari; Solihatun Solihatun (BAHASTRA, 2019)
The purpose of this study was (1) to describe the type of speech acts of Posyandu cadres Mawar VII and Posyandu Mawar IX Pademangan Barat North Jakarta in the information service process. (2) describe the principle of courtesy in Posyandu Mawar VII and Posyandu Mawar IX Pademangan Barat North Jakarta when the information service process takes place. The data used in this study are oral and written. Oral and written data is obtained by recording and recording the utterances of the cadres when carrying out information services. Data collection techniques in this study were carried out by referring to proficient free technique, recording techniques, and note taking techniques. The results of this study are that cadres do more polite speech acts using directive, representative, commissive, expressive, and declaration speeches. Second, cadres use four maxims, namely (1) wisdom maxim, (2) generosity maxim, (3) praise maxim, and (4) consensus maxim.